All types of coherent radiations, which arise in the collision of relativistic electrons with crystal - Morokhovskii, V.L. (Вопросы атомной науки и техники, 2015)
The general quantum theory, that describes all types of X-and-γ-rays coherent radiations, which arise in the collision of relativistic electrons with a crystal target, is described briefly. Such types of coherent radiations as: ordinary coherent bremsstrahlung and channeling radiation, emitted by a relativistic electron; different types of coherent polarization radiations, emitted by the crystal atoms and nucleus; the interference of these two types of coherent radiations can be described within the framework of the present theoretical model. Стисло викладена загальна теорія, яка пояснює всі типи когерентних рентгенівського та γ-випромінювань, які виникають при взаємодії релятивістських електронів з кристалічною мішенню. Такі типи випромінювань, як: звичайне когерентне гальмове випромінення та випромінення при каналюванні, випромінювані релятивістським електроном; різні види когерентних поляризаційних випромінень, джерелами яких є атоми та ядра кристала, - можуть бути описані в рамках даної теоретичної моделі. Кратко изложена общая теория, которая объясняет все типы когерентных рентгеновского и γ-излучений, возникающих при столкновении релятивистских электронов с кристаллической мишенью. Такие типы излучений, как: обычное когерентное тормозное излучение и излучение при каналировании, испускаемые релятивистским електроном; разные виды когерентных поляризационных излучений, испускаемых атомами и ядрами кристалла, - могут быть описаны в рамках данной теоретической модели.